Design of Hybrid System Power Management Based Operational Control System to Meet Load Demand - Zulfatman Has; Nurhadi Nurhadi; Fachmy Faizal (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
Renewable energy is an energy of unlimited sources that covering wind, sunshine and water, which can be used as sources of renewable power plants. These power plants give several advantages, but also some disadvantages, such as expensive generation costs, etc. The difficulty of being raised, due instability of renewable energy resources (RER). Aim of this study is to design power management of a hybrid system based on operational control system due to load demand. In this study, Power Management of Hybrid System used 3 power plants: Photovoltaic (PV), Wind Power, and Micro Hydro Power Plant (PLTmH), while Battery was employed as storage system. Main focus of the work was to determine the activation of each plant using Artificial Neural Network (ANN) method to fulfill the load demand. Matlab Simulink was employed to developed and simulate the ANN on the system. From results of simulation can be concluded that ANN can reach target accuracy level in 80%. When interconnecting the entire plant, the ANN experienced a misreading due to the voltage drop in each generator that affected the ANN input.